SEraMic: A semi-automatic method for the segmentation of grain boundaries. Issue 10 (August 2021) - Podor, R.; Le Goff, X.; Lautru, J.; Brau, H.P.; Massonnet, M.; Clavier, N.
Highlights: The SEraMic method is developed to automatically determine the grain boundary positions of monophasic ceramics. The SEraMic method is based on the recording of (BSE) SEM images with different tilt angles of a unique region of interest. The SEraMic plugin calculates and builds the segmented image of the grain boundaries from the set of tilted images. The method is easy to use and accurate when the average grain diameter is higher or equal to 0.25 μm. Abstract: The SEraMic method, implemented in the SEraMic plugin for Fiji or ImageJ software, was developed to calculate a segmented image of a ceramic cross section that shows the grain boundaries. This method was used to accurately and automatically determine grain boundary positions and further assess the grain size distribution of monophasic ceramics, metals, and alloys. The only required sample preparation is polishing the cross section to a mirror-like finish. The SEraMic method is based on at least six backscattered electron scanning electron microscopy images of a unique region of interest with various tilt angles ranging from -5° to +5°, which emphasises the orientation contrasts of the grains. Because the orientation contrast varies with the incident beam angle on the sample, the set of images contains information related to all the grain boundaries. The SEraMic plugin automatically calculates and builds a segmented image of the grain boundaries from the set of tilted images. The SEraMic method was compared with classical thermal etching methods, and it was applied to determine the grain boundaries in various types of materials (oxides, phosphates, carbides, and alloys). The method remains easy to use and accurate when the average grain diameter is greater than or equal to 0.25 μm.